Freud oggi: che cosa mi pare essenziale conservarne - Benvenuto, Sergio (Philosophy Kitchen - Rivista di filosofia contemporanea, 2020)
The author, a psychoanalyst, essentially distinguishes three fundamental phases of psychoanalysis in the over 100 years since its inception. The first, hinged on Freud and his followers, was founded on a metapsychology centered around the notion of drive and repetition; at the time, psychoanalysis understood itself not as one psychological theory, but as Psychology tout court. A second phase assumed various forms and directions—from Winnicott to Lacan, from Bion to Laplanche—where transference assumed an ever more fundamental significance, and where a sort of primacy of the other (the other as variously understood) established itself in both practice and in analytic theory. We have now entered a third phase of a still imprecise character which has for the time being uncovered only partial or insufficient theorisations, and which aims more at recognising the analytic practice as it is actually practiced rather than instituting a good analytic practice. In this context, the Freudian metapsychology is viewed as myths, albeit perspicuous, to understand in an essentially metaphoric sense. One expects more of a theory on psychoanalysis than of psychoanalysis.